2003
DOI: 10.1038/sj.bjc.6601388
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and risk of non-Hodgkin lymphoma subtypes among women

Abstract: Previous studies of the relationship between cigarette smoking and non-Hodgkin lymphoma (NHL) have yielded conflicting results, perhaps because most studies have evaluated the risk for all NHL subtypes combined. Data from a population-based case -control study conducted among women in Connecticut were used to evaluate the impact of cigarette smoking on the risk of NHL by histologic type, tumour grade, and immunologic type. A total of 601 histologically confirmed, incident cases of NHL and 718 population-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
2

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 31 publications
6
35
2
Order By: Relevance
“…However a positive link in ever smoking women was perceived for follicular lymphoma. 17 Other publications 18,20,[29][30] have contributed results of close resemblance. In a pooled analysis of nine case-control studies 31 smoking was associated with a slightly increased risk of NHL overall.…”
Section: Discussionmentioning
confidence: 80%
“…However a positive link in ever smoking women was perceived for follicular lymphoma. 17 Other publications 18,20,[29][30] have contributed results of close resemblance. In a pooled analysis of nine case-control studies 31 smoking was associated with a slightly increased risk of NHL overall.…”
Section: Discussionmentioning
confidence: 80%
“…Of interest was a small but significant increase in risk of NHL after bladder cancer, which could also indicate some joint exposures for the two cancers. Although smoking is an attractive putative common risk factor between NHL, bladder and lung cancer, the evidence for a role of smoking in NHL has been very limited until now, with only few studies suggesting that smoking may be associated with follicular NHL (Herrinton and Friedman, 1998;Parker et al, 2000;Morton et al, 2003;Stagnaro et al, 2004).…”
Section: Treatment Effectsmentioning
confidence: 99%
“…368,369,373,374,376,382,388,[394][395][396][397][398][399] In a recent pooled analysis of 9 case-control studies, Morton et al 398 reported a significant inverse association with alcohol (pooled OR 5 0.83, 95% CI: 0.76-0.89), which did not vary with frequency or duration of intake, or by type of alcoholic beverage (OR for beer only, compared to nondrinkers 5 0.85, 95% CI: 0.76-0.95; OR for wine only 5 0.85, 95% CI: 0.74-0.99; OR for liquor only 5 0.90, 95% CI: 0.74-1.09). In a subgroup analysis of 4 of the studies with sufficient data, relative risk estimates were lower for current drinkers (pooled OR 5 0.73, 95% CI: 0.64-0.84) than for former drinkers (pooled OR 5 0.95, 95% CI: 0.80-1.14), compared to nondrinkers.…”
Section: Lifestyle and Personal Factors Tobacco And Alcohol Usementioning
confidence: 99%